Analisis bibliometrik peran tata kelola TI dalam transformasi digital perusahaan - Hibatullah, Muhammad Naufal; Zaman, Syahiduz (Maliki Interdisciplinary Journal, 2024)
In the rapidly evolving digital era, digital transformation is imperative for companies to remain competitive. Effective IT Governance plays a crucial role in the success of this digital transformation. This study aims to map the development and research trends related to the role of IT Governance in corporate digital transformation through bibliometric analysis. Data was collected using Publish or Perish and analyzed with VOSviewer. Results indicate three main clusters in this research: IT Governance and change management, information security and IT risk, and new technology implementation. Overlay and density visualizations highlight the most prominent research areas and their intensities. Trend analysis shows an increased focus on IT security, AI and IoT implementation, and leadership roles. This study contributes to academics by identifying future research directions, to practitioners by understanding trends and best practices, and to policymakers by developing effective policies. Using bibliometric analysis and visualization tools, this research reveals patterns, trends, and gaps in the literature, providing valuable contributions to the development of knowledge and practice in IT Governance and digital transformation.